2018
DOI: 10.5897/ajar2018.13403
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evaluation of irrigation practice in Nigeria: Past, present and future prospects

Abstract: Irrigation practice across the world is vital to successful green revolution all year round to achieving sustainable development goals in food security, socioeconomic and rural development. However, irrigation practice in Nigeria has not achieved the set goals despite the huge investment involved. Moreover, the level of investment and abundant water resources ought to have expedited the goals of food self-sufficiency and socioeconomic development in the country. This review attempts to uncover the underline is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…These are initiatives taken by government institutions themselves or in partnership with various development partners (Chukwuemeka and Nzewi 2011) (Chukwuemeka and Nzewi 2011;Ogunjimi and Adekalu 2002). This period of the ADP heralded massive deployment of tube well or wash-bore smallholder irrigation practices in multiple watersheds in Northern Nigeria, where irrigation using shallow groundwater was feasible (Adelodun and Choi 2018). Similarly, in the southern states where the possibility of using tube well technology is remote-within the Ogun watershed, for instance-several small dams and reservoirs for irrigation and rural water supply were constructed under the Oyo North Agricultural Development Program (Chukwuemeka and Nzewi 2011;Daneji 2011).…”
Section: Agricultural Development In Nigeria: a Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…These are initiatives taken by government institutions themselves or in partnership with various development partners (Chukwuemeka and Nzewi 2011) (Chukwuemeka and Nzewi 2011;Ogunjimi and Adekalu 2002). This period of the ADP heralded massive deployment of tube well or wash-bore smallholder irrigation practices in multiple watersheds in Northern Nigeria, where irrigation using shallow groundwater was feasible (Adelodun and Choi 2018). Similarly, in the southern states where the possibility of using tube well technology is remote-within the Ogun watershed, for instance-several small dams and reservoirs for irrigation and rural water supply were constructed under the Oyo North Agricultural Development Program (Chukwuemeka and Nzewi 2011;Daneji 2011).…”
Section: Agricultural Development In Nigeria: a Historical Perspectivementioning
confidence: 99%
“…While private irrigation based on tube wells proved a huge success in parts of Northern Nigeria (Adelodun and Choi 2018;Moro and Onoja 2006), major limitations have hindered the small dams and reservoirs constructed under the ADP as a result of poorly equipped, or even absent, irrigation infrastructure such as headworks and conveyance structures. This was similar to the challenges observed with large-scale irrigation schemes (Enplan Group 2004) and has contributed to the poor use of small reservoirs.…”
Section: Agricultural Development In Nigeria: a Historical Perspectivementioning
confidence: 99%
“…Low-lying and seasonal flooded areas can grow rice. The country has 68 million hectares of arable land, abundant freshwater resources covering about 12 million hectares, and an ecological diversity which enables the country to produce a wide variety of crops (Bashir & Kyung-Sook, 2018).…”
Section: 22mentioning
confidence: 99%
“…Drought caused by climate change, particularly in the eastern parts, has resulted in environmental conditions such as decreased pasture, soil, and surface inflow of water, particularly to Lake Chad, causing it to shrink in the region. This has resulted in overpopulation of livestock in the Chad basin, as well as a southward shift, complicating farmer-fisherman-herder conflicts (Bashir & Kyung-Sook, 2018). Empirical studies (Ubani Onyejeke, 2013;Ojimba and Iyagba, 2012) have found that gas flaring and crude oil spillages and pollution have a negative impact on agricultural yield, farmland loss, and the degradation of fish and other aquatic resources in the Niger Delta region (Adekola & Mitchell, 2011).…”
Section: Demographic and Security Impactsmentioning
confidence: 99%
“…Irrigation practice across the world is vital to successful green revolution all year round to achieving sustainable development goals in food security, socio-economic and rural development [1]. Because, irrigation plays an essential role in stabilizing crop production by either supplementing or replacing the need for natural precipitation and it makes agriculture more confidential, stabilizes crop production by protecting against drought [2].…”
Section: Introductionmentioning
confidence: 99%